Micromorphological Aspects of the Development of Rubella Virus in BHK-21 Cells - Edwards, Mercedes R. (1969)
Sequential effects of rubella virus infection in BHK-21 cells were studied by electron microscopy of thin sections of control and infected cells, 2 to 7 days after infection. Vacuolization of cytoplasm in Golgi areas apparently preceded budding of virions from vacuole membranes and involvement of the endoplasmic reticulum. Newly formed endoplasmic reticulum cisternae encircled and segregated virionforming vacuoles together with other cellular elements. Large vacuolar complexes with numerous virus particles developed, and virus release from these areas occurred with disruption at the cell periphery. The viral particles, with a mean diameter of about 56 nm, consisted of an electron-dense core surrounded by a less dense capsid, enveloped by a typical unit membrane derived from the vacuole membrane.